The Impact of the Development of Islamic Banking in West Sumatra Province in Review of Maslahah Mursalah - Okto Viandra Arnes (International Journal of Sharia Studies, 2025)
The development of Islamic Banking in West Sumatra Province has become a significant phenomenon that impacts various economic and social aspects in the region. This research aims to explore the impact of such development with a focus on the Maslahah Mursalah perspective, which involves general welfare without specific restrictions in Islamic law. The research methods included a literature study to understand the theories and findings of previous research, surveys and interviews to collect data from the community, customers, and relevant stakeholders. Data analysis was conducted quantitatively and qualitatively to gain a holistic understanding of the impact of Islamic Banking. The results showed that the development of Islamic Banking in West Sumatra Province has contributed positively to the economic empowerment of the community. Through financial services that comply with sharia principles, financial accessibility has increased, especially among micro and small businesses. Islamic financial literacy has also increased, enabling people to understand and adopt sharia principles in their financial lives. This research presents a comprehensive picture of the impact of the development of Islamic Banking in West Sumatra Province from the perspective of Maslahah Mursalah. The implications of the results of this study can provide policy direction and contribute to a better understanding of the role of Islamic banks in achieving general welfare without overriding the principles of sharia.